2015
DOI: 10.1038/leu.2015.210
|View full text |Cite
|
Sign up to set email alerts
|

Altered mesenchymal niche cells impede generation of normal hematopoietic progenitor cells in leukemic bone marrow

Abstract: Degeneration of normal hematopoietic cells is a shared feature of malignant diseases in the hematopoietic system. Previous studies have shown the exhaustion of hematopoietic progenitor cells (HPCs) in leukemic marrow, whereas hematopoietic stem cells (HSCs) remain functional upon relocation to non-leukemic marrow. However, the underlying cellular mechanisms, especially the specific niche components that are responsible for the degeneration of HPCs, are unknown. In this study, we focused on murine bone mesenchy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 41 publications
3
35
1
1
Order By: Relevance
“…More recently, CML and ALL mouse models have shown that a reduction in SDF-1 levels in BM is responsible for impaired LT-HSC or human CD34+ homing and retention [17,18,19,20]. This apparently modest change in cytokine production by stromal cells has profound effects on HSC biology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, CML and ALL mouse models have shown that a reduction in SDF-1 levels in BM is responsible for impaired LT-HSC or human CD34+ homing and retention [17,18,19,20]. This apparently modest change in cytokine production by stromal cells has profound effects on HSC biology.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced SDF-1 secretion, essential chemokine for HSC homing and retention, and an increase of other chemokines and cytokines by BM stromal cells are responsible for impaired support for HSC and a selective growth advantage for leukemic cells [17,18,19]. Leukemic cells induced an SCF-dependent CD34+ progenitors’ displacement to novel malignant microenvironments [20].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is becoming clear that progressive changes in both, cell composition and function of the microenvironment may govern abnormal progenitor cell activity and drive to establishment of exclusive structures suitable for leukemic cell proliferation but incompatible for sustaining normal hematopoiesis, that ultimately lead to disease (4, 22–26). Previous studies in mice models and leukemia patients revealed that some of the BM microenvironmental alterations include an increased concentration of SCF and a decreased production of CXCL12 (2, 24, 27).…”
Section: Introductionmentioning
confidence: 99%
“…In a Notch-induced T cell ALL model, bone marrow-derived MSCs isolated from T cell ALL-bearing mice have decreased expression of hematopoietic stem and progenitor cell (HSPC) niche-associated genes and impaired functionality of Lineage − Sca-1 + cKit + (LSK) stem cells after short term co-culture (Lim, et al, 2016). More specifically, there are examples of changes in bone marrow stromal cells in the osteoblastic, neural, and endothelial compartments.…”
Section: Modulation Of the Hsc Niche By Hematopoietic Malignancymentioning
confidence: 99%